The Structure of FemXWv in Complex with a Peptidyl‐RNA Conjugate: Mechanism of Aminoacyl Transfer from Ala‐tRNAAla to Peptidoglycan Precursors1. Issue 28 (6th June 2013) - Fonvielle, Matthieu; Li de La Sierra‐Gallay, Inés; El‐Sagheer, Afaf H.; Lecerf, Maxime; Patin, Delphine; Mellal, Dénia; Mayer, Claudine; Blanot, Didier; Gale, Nittaya; Brown, Tom; van Tilbeurgh, Herman; Ethève‐Quelquejeu, Mélanie; et al.
<x xml:space="preserve">Abstract</x> To gain insight into the catalytic mechanism of non‐ribosomal amino acid transferases, peptidyl‐RNA conjugates were synthesized for co‐crystallization with FemXWv of Weissella viridescens, which transfers L‐Ala from Ala‐tRNAAla to the peptidoglycan precursor UDP‐MurNAc‐pentapeptide. The structure of the resulting complex and mutational studies revealed the mechanism by which FemXWv binds its substrates for substrate‐assisted catalysis and stabilization of the tetrahedral intermediate.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>